An empirical analysis of sport for mental health from the perspective of a factor analysis approach - Zhou, Lan; Lee, Sang-Ho; Cao, Youshen (Frontiers in Psychology, 2022)
In the process of compulsory education, middle school and high school period is a key stage in the gradual formation and development of students' psychology and body, but due to the large audience of China's education, the competition is more intense, which inevitably causes a lot of students to focus on exam-oriented education and neglect physical health, especially in recent years, the mental health issues of increasing concern. Through the research situation of mental health in China and the concept of mental health quality, this paper analyzes the problems of sports and mental health, and puts forward some corresponding suggestions for the problems, which has reference significance for promoting students' mental health.